Sistema de control en el procesamiento de materia prima como soporte a la toma de decisiones en la gestión de compra basado en web service. - Arciniegas, Alexandra (2011)
Actually the Cafeica counts on a system that manager the administration general of the company, which consists of options of maintenance, consult and report for the areas of Administration. The co-workers of these areas are the direct users of the system and because of the type of information that they hand and proper functions of responsibility, the unique with access to the same place. Additionally, in Cafeica as a part of the continuation, measurement and performance indicators are reported that permit to go measuring the management of raw material purchase “cacao”. Actually this process represents a great operative load specially on the control of raw material purchase of cacao and audits, because there is no centralized information. Because of which, when any co-workers requires a very general must apply it and wait by his deliver in agree with the time established in norms of the management. The alternative proposed for the company is the development of a Web Site that permit to the co-workers have at their disposal information in line and several times that they require it, related with the purchasing management and the operational area with the control of the process of the raw material of cacao to automation of the process of the performance and the productivity.